Pemetaan Daerah Rawan Kecelakaan Dan Solusi Penanganan Untuk Mengurangi Angka Kecelakaan Di Kota Bengkulu - Elly Tri Pujiastutie (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
The accident in the road is suddenly happen and intuitively involve vehicle with or without other road walker that is effect human victim with or without loss property. Many efforts already done to avoid and anticipation the accident, but the accident still happened. The data that is easy to access will be help handling. Information system give information about location the sensitive accident place with collect history data from the sensitive accident location. The information is used to analysis how to handling that area and to be standard for getting the data with expectation the accident number will be decreased in Bengkulu city. The mapping in the sensitive accident area that is easy to access lade accident data and condition in the road for make handling policy and priority in area which is happened the accident in Bengkulu city. Least three years, Pariwisata, Baai Island, and Sungai Hitam road have high accident number. Accident data rate from 2012 until 2014 are in Pariwisata 4.04;2.69;2.31,in Sungai Hitam 2,14; 3,57; 3,57 and Baai Island 1,18; 0,59; 0,59. Elongated and transverse pieces on the body of the road to know condition the road, such as there is no side channel to deliver water which will affect the flexible pavement that is very vulnerable to water because it will destroy structure and pavement layer. Some roads have been damaged, for example: hole, cracked, bumpy road. Because of that condition, it must be maintenance soon. Some of the road, there is no median of the road. Median installation will be very helpful to reduce accident such as: avoid crash face to face, right angle accident. Installation speed limiting signs will be very helpful to reduce the accident number